Toward a tiered regulatory framework for the prospective aquatic effect assessment of pesticides in (Neo)tropical areas - Daam, Michiel A. (2023)
Research and regulatory interest into (Neo)tropical aquatic pesticide ecotoxicology has increased considerably over the past few years. However, pesticide effect assessment frameworks in (Neo)tropical areas remain largely undeveloped and as such not implemented. The present study provides an overview of studies into the comparison of pesticide sensitivity between (Neo)tropical and temperate aquatic taxa. Recommended assessment factors to be applied to temperate toxicity data for use in tropical effect assessments differ significantly between these studies. Shortcomings and bottlenecks of available pesticide sensitivity comparison studies based on results from bioassays, species sensitivity distributions, and model ecosystem studies are scrutinized. Current data lacks and (subsequent) indications for future research are also covered. Ultimately, implications for procedures aimed at the derivation of regulatory acceptable concentrations for pesticides in (Neo)tropical edge-of-field surface waters are discussed. Integr Environ Assess Manag 2022;00:1–10. © 2022 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC).